Actividades antropogénicas en la subcuenca del Río Carrizal y su incidencia en la calidad del agua. - Triviño Acosta, Carlos Andrés (2018)
The incidence of anthropogenic activities in the water quality of the sub-basin of the Carrizal River was evaluated through the application of surveys to the communities under study, by means of proportional affixation sampling. For the weighting of the water quality, the ICA – NSF methodology was used, establishing fifteen sampling stations along the river, taking as control point the river Severino, Membrillo and the Sixto Durán Ballén reservoir, these being the main contributing tributaries to the Carrizal river. The water quality was "weighted" before and after the communities: Quiroga, Measles, El Paraíso, Calceta, La Estancilla and Tosagua, for the calculation of the Index, ICATEST software V1.0 was used, revealing the presence of coliforms fecal in a large part of the monitoring stations. In addition to high concentrations of Nitrates and Phosphates. The levels of contamination according to the ICA – NSF varied from 54.39 to 60.62, that is to say average classification, developed by Brown (1970). As productive activities, "agriculture" and "livestock" were highlighted, with a 20% impact on water quality. Being the use of latrines, an anthropogenic effect that produces greater effect on the quality of the river by 51% to the banks of it. Using the Student's "t" test, the hypothesis is accepted. taking as tail value (2,228), this means that the value of t is in the range of minus 2,228 obtaining a value of t = 0.439 that is (-2,228< 0,439 > 2,228).